Gender Mainstreaming and Women Empowerment – Reflections and Upshots from fishing industry of Kerala - Shyam.S.Salim (Discovery Agriculture, 2013)
Mainstreaming aims at incorporating gender concerns as an integral element in the implementation, monitoring and evaluation of policies and programmes so that benefits are shared equally and inequality isn’t perpetuated. (UNDP, 2008) opined that investing in women competencies and empowering them to exercise their choice is the surest way to sustain economic growth and development. In India, fisheries sector provides a livelihood for women as a source of supplementing fisher household income by their engagement in pre and post-harvest activities including marketing. The fisherwomen in Kerala assume significance due to their involvement in fish related activities leading to distribution, availability and value addition. The study focused the economic, social, political and legal empowerment of fisherwomen involved in processing and marketing across four occupational groupsviz. fish retailer, fish vendor, dry fish makers, and value added fish producers and was based on primary data collected from fisherwomen households. The study analyzed empowerment levels using scoring indices and composite empowerment index for fisherwomen categories were estimated. The social and economic empowerment level was high with freedom in decision making and household expenditure. Handling, transporting and storage operations exhibited highest level of discriminations. SHG’s and co-operatives were major networking institutions which augmented empowerment levels. Market intelligence and news were concerns of continuing discriminations. The results indicated that the fisherwomen in Kerala possessed healthier composite fisherwomen empowerment index. Nevertheless appropriate institutional arrangements ensuring equal opportunities in fish marketing and processing and priority for institutional credit access will mend gender discrimination of fisherwomen for future.